2019
DOI: 10.1021/acs.jafc.8b05417
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Yields and N2O Formation from Photolysis of Solid Films of Neonicotinoids

Abstract: Neonicotinoids (NN), first introduced in 1991, are found on environmental surfaces where they undergo photolytic degradation. Photolysis studies of thin films of NN were performed using two approaches: (1) transmission FTIR, in which solid films of NN and the gas-phase products were analyzed simultaneously, and (2) attenuated-total-reflectance FTIR combined with transmission FTIR, in which solid films of NN and the gas-phase products were probed in the same experiment but not at the same time. Photolysis quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 58 publications
1
21
1
Order By: Relevance
“…This product in the solid phase was observed also for a number of NNs (Figure 8), all of which form N 2 O in the gas phase when irradiated as thin films. 46 Dows 63 and Yamada and Person 64 showed that condensed N 2 O at 80 K has a single peak in this region, with some variation in peak shape, and Hisatsune 65 showed a temperature dependence for this peak's location and shape. Thus, we assign the 2222 cm −1 peak seen in the solidonly spectrum to N 2 O that is trapped in the KBr pellet solid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This product in the solid phase was observed also for a number of NNs (Figure 8), all of which form N 2 O in the gas phase when irradiated as thin films. 46 Dows 63 and Yamada and Person 64 showed that condensed N 2 O at 80 K has a single peak in this region, with some variation in peak shape, and Hisatsune 65 showed a temperature dependence for this peak's location and shape. Thus, we assign the 2222 cm −1 peak seen in the solidonly spectrum to N 2 O that is trapped in the KBr pellet solid.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies in our lab showed no significant differences between results in pure N 2 and in dry ultra-zero air. 46 The pellets were probed at measured time intervals using FTIR spectroscopy (Mattson Galaxy 5020 FTIR, cooled MCT detector) with 64 coadded scans at 0.5 cm −1 resolution. Samples were irradiated using either a 254 nm low-pressure mercury lamp (UVP, CPQ-5851) or one of two mercury lamps with organic phosphor coatings that gave broadband emissions.…”
Section: Preparation and Infrared Analysis Of Kbr Pelletsmentioning
confidence: 99%
“…Quantum yields for the loss of nitroguanidine in thin solid films were recently measured to be of the order of ∼10 −3 at wavelengths above 300 nm . However, in aqueous solution the quantum yields can be one to two orders of magnitude higher .…”
Section: Heterogeneous Reactions Of Neonicotinoid Pesticides In the Tmentioning
confidence: 99%
“…While the amount of nitrous oxide generated from NN photolysis on a global scale is small compared to other sources and thus expected to have little impact on climate, the photolysis of the solid NN is another example of a multiphase atmospheric reaction that generates gas phase products from the condensed phase.…”
Section: Heterogeneous Reactions Of Neonicotinoid Pesticides In the Tmentioning
confidence: 99%
“…Once in the atmosphere, the fate of pesticides is dictated by dry and wet deposition, 14 as well as by the chemical processes including photolysis and oxidation initiated by atmospheric oxidants such as O 3 , OH, and NO 3 radicals. [15][16][17][18][19][20] Wet and dry deposition are physical removal processes and will not be removed from the environment. In turn, the efficiency of photolysis depends on three factors: absorption cross section, quantum yield for photo-induced reactions, and actinic ux of solar radiation.…”
Section: Introductionmentioning
confidence: 99%